Determinants of Regional Household Final Consumption Expenditure in Indonesia - Sugiarto, Sugiarto; Wibowo, Wisnu (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
The Indonesian economy, both at the national and regional levels, tended to experience a slowdown during 2010-2019. From the demand side, household final consumption expenditure (HFCE) is the primary cause of the slowdown. Therefore, various efforts are needed to maintain and improve HFCE. One of these efforts is to keep the stability of the macroeconomic factors that influence it. This research aims to reveal the determinants of regional HFCE in Indonesia. The determinants of HFCE were investigated using a dynamic panel data regression model with the first-difference Generalized Method of Moments (FD-GMM) approach and applied to data from 33 provinces during 2010-2019. The application of FD-GMM provides valid and consistent estimates. The results of the parameter significance test provide evidence that the lagged real HFCE, real gross regional domestic product (GRDP), and government spending have a significant positive impact on real HFCE. Meanwhile, both the inflation and unemployment rates had significantly negatively impacted. Thus, the role of policymakers in maintaining the stability of the five macroeconomic factors is necessary so that HFCE increases and the economy can grow even higher.